Identifying Challenges and Developing Visions - Technology Foresight in Hungary - Attila Havas (Hungarian Academy of Sciences, Institute of Economics, 2002)
TEP, the Hungarian Technology Foresight Programme, was launched in 1997, as the first one in Central and Eastern Europe, to provide inputs to a national strategy by identifying socio-economic challenges and developing broad visions for the future. Specifically, it was aimed at analysing Hungarys current strengths and weaknesses, developing scenarios (visions) and formulating policy proposals to improve quality of life and the longterm international competitiveness. This presentation first briefly defines the concept and methods of (technology) foresight, and highlights some reasons why it is a useful policy tool, followed by a brief account of the objectives and methods of TEP. Then, summarising the results, Sections 3 and 4 provide an overview of the transition process (institutional changes as well as economic developments) and the current socio-economic challenges, respectively. Changing the time horizon, 3 long-term macro scenarios are discussed in Section 5, together with policy recommendations developed by TEP so as to achieve the most desirable but still feasible vision. Section 6 summarises the results of the dissemination and implementation phase of TEP. Finally, the concluding section highlights the benefits of foresight to assist decision-makers; some general difficulties concerning its design, methodologies and implementation of its results; as well as specific Hungarian problems, due to the legacy of planning.
Keywords: 330